Acquisition, Preference and Follow-up Comparison Across Three AAC Modalities Taught to Two Children with Autism Spectrum Disorder. Issue 2 (4th March 2017) - McLay, Laurie; Schäfer, Martina C. M.; van der Meer, Larah; Couper, Llyween; McKenzie, Emma; O'Reilly, Mark F.; Lancioni, Giulio E.; Marschik, Peter B.; Sigafoos, Jeff; Sutherland, Dean
Abstract: Identifying an augmentative and alternative communication (AAC) method for children with autism spectrum disorder (ASD) might be informed by comparing their performance with, and preference for, a range of communication modalities. Towards this end, the present study involved two children with ASD who were taught to request the continuation of toy play by: (a) signing MORE, (b) exchanging a picture card representing MORE, and (c) touching a MORE symbol from the screen of a speech-generating device. The children were also given opportunities to choose among the three modalities to identify their preferred method of communication. Both children performed better with picture exchange and the speech-generating device than with manual signing, but had variable performance during follow-up. Both children more often chose the speech-generating device, suggesting a preference for that modality. We conclude that concurrent intervention across several communication methods can generate data to inform the selection of an AAC modality.